The Impact of Lifestyle Theory Approach in Housing Choices in Malaysia - Azizah, Ismail; Ahmad Tajjudin, Rozman; Wilson Rangga, Anthony Jiram; Ahmad Fawwaz, Ahmad Saleh (Human Resource Management Academic Research Society, 2024)
The demand for housing that follows current lifestyle-housing concept has been growing. This research studies using Lifestyle Theory approach to analyse consumer behaviour in making housing choices. The objective of this study is to identify the lifestyle characteristics in housing development and housing preference that common in all the lifestyle characteristics. The methodology used to collect the primary data from respondents is the questionnaires while literature review from journals and reports are the secondary data for the research. The sample for this research is 100 correspondents who are randomly distribute using Google form survey due to COVID-19 Movement Control Order. The data gathered was analyse using descriptive analysis and Cross Tabulation and Correlation analysis using Statistical Package for Social Science (SPSS) software to get the final result. The findings show active lifestyle, perfection lifestyle and privacy lifestyle are significant with house management services and size and space of housing. The novelty of this research suggests that these results can be used as a guideline to developers offering lifestyle concept housing with appropriate living space and excellent management services. The next research on housing preferences we should determine appropriate size and living space that are accommodable to the consumers.